A Qualitative Study of a Mentalization-based Group for Borderline Patients. (June 2015) - Sagen Inderhaug, Tryggve; Karterud, Sigmund
In this article we present a video-based explorative study of three consecutive mentalization-based group therapy (MBT-G) sessions at a Norwegian Mental Health Centre. MBT-G has its roots in group analytic psychotherapy, but is modified to avoid the chaotic and destructive processes often encountered in groups consisting of severely personality disordered patients. Among the most notable differences from the Foulkesian group analytic approach are the therapists handling of authority and a 'not-knowing stance' (as opposed to an interpretative stance). Contrary to our expectations we found the typical chaotic borderline group processes that MBT-G was designed to avoid. An in-depth examination of the data, employing qualitative Thematic Analysis, revealed that the therapists failed to establish themselves as authoritative leaders of the group and misconstrued the 'not-knowing stance'. We present transcripts of some typical sequences and discuss their clinical and therapeutic implications.